Muscle architecture and morphology as determinants of explosive strength - Maden-Wilkinson, T. M.; Balshaw, T. G.; Massey, G. J.; Folland (European Journal of Applied Physiology, 2021)
Purpose: Neural drive and contractile properties are well-defined physiological determinants of explosive strength, the influence of muscle architecture and related morphology on explosive strength is poorly understood. The aim of this study was to examine the relationships between Quadriceps muscle architecture (pennation angle [TP] and fascicle length [FL]) and size (e.g., volume; QVOL), as well as patellar tendon moment arm (PTMA) with voluntary and evoked explosive knee extension torque in 53 recreationally active young men. Method: Following familiarisation, explosive voluntary torque at 50 ms intervals from torque onset (T50, T100, T150), evoked octet at 50 ms (8 pulses at 300-Hz; evoked T50), as well as maximum voluntary torque, were assessed on two occasions with isometric dynamometry. B-mode ultrasound was used to assess TP and FL at ten sites throughout the quadriceps (2-3 sites) per constituent muscle. Muscle size (QVOL) and PTMA were quantified using 1.5 T MRI. Result: There were no relationships with absolute early phase explosive voluntary torque (= 50 ms), but ThetaP (weak), QVOL (moderate to strong) and PTMA (weak) were related to late phase explosive voluntary torque (= 100 ms). Regression analysis revealed only QVOL was an independent variable contributing to the variance in T100 (34%) and T150 (54%). Evoked T50 was also related to QVOL and ThetaP. When explosive strength was expressed relative to MVT there were no relationships observed. Conclusion: It is likely that the weak associations of ThetaP and PTMA with late phase explosive voluntary torque was via their association with MVT/QVOL rather than as a direct determinant.